Diagnostic performance of angiography-derived FFR in patients presenting with NSTE-ACS. (3rd October 2022) - Skalidis, I; Meier, D; Muller, O; Fournier, S
Abstract: Background: Precise non-invasive methods to measure fractional flow reserve (FFR) are actively being explored, aiming to avoid the use of invasive pressure wire and the administration of hyperaemic stimulus. Coronary angiography-derived FFR (FFRangio) has already proved its diagnostic performance in validation studies in the context of stable coronary artery disease. However, its applicability in the context of non-ST-segment elevation acute coronary syndromes (NSTE-ACS) has yet to be established. Purpose: The study sought to determine the diagnostic performance of FFRangio in patients presenting with NSTE-ACS and evaluate if it could serve as a reliable alternative to invasive FFR. Methods: This study is a prospective, single-center, single-arm, double-blinded clinical study comparing the FFR calculated by FFRangio to invasive FFR and it represents a sub-study of a protocol evaluating the diagnostic performance of FFR-CT in NSTE-ACS patients, whose design and rationale has been previously published. Invasive FFR was measured in all angiographically intermediate lesions (30%-70% stenoses) in NSTE-ACS patients and was then compared to FFRangio which was measured in the same position, by a blinded operator. The study primary endpoints were the per lesion diagnostic characteristics of FFRangio using invasive FFR as the standard of reference. A value of ≤0.80 was considered as the threshold for a positive result (i.e. functionally significant lesion) for both invasive and FFRangio. Results: Among the 46 NSTE-ACS patients included in the study according to the inclusion/exclusion criteria, a total of 60 vessels underwent invasive FFR measurement. The mean value of invasive FFR was 0.83±0.3 with 36% being positive. The mean FFRangio was 0.82±0.1 with 36% being positive. FFRangio showed a sensitivity of 95.5%, a specificity of 97.4% and a diagnostic accuracy of 96.7% to detect the functional significance of an angiographically intermediate stenosis. Moreover, it showed similar diagnostic performance across all three coronary arteries. FFRangio values correlated well with invasive FFR measurements (r=0.83, P<0.001) and the Bland–Altman 95% confidence limits were between −0.12 and 0.10. Conclusions: This study adds to the limited knowledge on the validity of FFRangio in the context of acute coronary syndromes and demonstrates excellent diagnostic performance as well as strong correlation to the invasive FFR for in the setting of NSTE-ACS. It contributes to the growing body of evidence suggesting that FFRangio can precisely calculate FFR in a wide range of clinical situations thus diminishing the risks of an invasive procedure and the use of hyperaemic agent. Since it is non-invasive, simple and cost-effective, the use of FFRangio could be routinely considered to guide treatment decision in angiographically intermediate coronary lesions in the context of NSTE-ACS. Funding Acknowledgement: Type of funding sources: None.